Membangun Server NVR berbasis Open-Source menggunakan ShinobiCE (Studi Kasus DISKOMINFO Boyolali) - Bagus Pramono; Indrastanti Ratna Widiasari (KITA Institute, 2023)
One of the well-known software with high quality content delivery standards is Flash Player. Flash Player has a wide user base, with over 90% internet penetration on connected computers. Since December 31, 2021 Adobe announced that Adobe Flash Player is no longer supported and Adobe has also blocked Flash content from running on browsers so that users can no longer experience the advantages of Flash Player. a player allowed by the browser. Based on these problems, a solution is needed so that Flash Player can run in the browser, namely by building an NVR server using ShinobiCE. Through this research, an Open-Source-based NVR server was built using ShinobiCE so that CCTV can accommodate more with maximum resolution quality and the results of streaming links that can be used for live browser streams.